PERSPEKTIF MASYARAKAT DEWASA MENGENAI COVID-19: SEBUAH STUDI FENOMENOLOGI DESKRIPTIF - Grace Fresania Kaparang; Ivanna Junnamel Manopo; Aprilina Awing (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Bengkulu, 2022)
T The COVID-19 pandemic in the globalization era has brought infodemic resulting from easy access to information on various social media platforms followed by the emergence of various responses in the community in this pandemic. The study aimed to explore the perspective of the adult community in Airmadidi Bawah of the current COVID-19 pandemic. This is a descriptive phenomenology qualitative design study based on the Husserlian philosophy and Colaizzi's method. The sampling technique is a simple random sampling technique that reached data saturation in five participants. Two themes emerged from the thematic analysis, which was the cognitive perspective and the emotional perspective. Overall, there are several cognitive perspectives that the community are less likely to capture. Then from an emotional perspective, there were two sub-themes, namely positive and negative emotions, but negative ones dominate. It is recommended that there be thorough and detailed education from the local government and related agencies for the people in the local area regarding COVID-19 to reduce the inaccurate perception of the local community to reduce unnecessary fear in the community.